Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Resimen III Pasukan Pelopor - Hotmauli Angelina Nainggolan; Helmy Ivan Taruna (Master Manajemen, 2024)
This research is entitled "The Influence of Motivation and Work Discipline on the Performance of Employees of the III Regiment of the Pioneer Force". This study aims to see the influence of motivation and work discipline on employee performance partially and simultaneously. A sample taken for respondents. This study is a quantitative research by testing hypotheses using SPSS version 20. The results of the t-test (partial) test on the motivation variable showed that t counted 5.546 > t table 2.002 and a significant value of 0.000 < 0.05, meaning that the motivation variable partially affected and significant on the performance of employees of the III Passukan Pioneer Regiment. The results of the t-test (partial) test on the work discipline variable showed a t count of 4.973 > 2.002 and a significant value of 0.000 < from 0.05, meaning that the work discipline variable partially affected and significant on employee performance III Regiment of the Pioneer Force. Based on the output results of SPSS version 20, the results of the f test (simultaneous) test show that the F value is greater than the f table or 441.704 > 3.16 and the significant value is 0.000 < 0.05. Therefore, it can be concluded that motivation (X1) and work discipline (X2) together have a significant and significant effect on employee performance (Y).